The importance of anatomical region of local anesthesia for prostate biopsy; a randomized clinical trial - Akdere, Hakan; Burgazli, K M; Aktoz, T; Acikgoz, A; Mericliler, M; Gözen, Ali Serdar (European review for medical and pharmacological sciences, 2013)
INTRODUCTION: In our study, the efficiency and reliability of lidocaine (1 cc/1%) application during transrectal ultrasound-guided (TRUS) prostate biopsy to levatores prostate was studied. Levatores prostate was visualized on a cadaver dissection previously.
Gesehen am 07.05.2021